Pengaruh Leverage, Ukuran Perusahaan, dan Profitabilitas Terhadap Tax Avoidance - Yulia Ribuna Br Bangun; Annisa Khairani; Salshabilla Nayma; Abel Sonia S; An Suci Azzahra (CV. ITTC INDONESIA, 2025)
The effect of leverage, company size, and profitability on tax avoidance efforts in businesses engaged in the industrial sector. Leverage is measured by DAR, company size is measured by Ln (total assets), Profitability is measured by ROA and tax avoidance by ETR. The focus of quantitative research is industrial companies listed on the IDX. The number of samples collected using the purposive method was 19. Secondary data was used from the 2020-2024 financial statements. To complete this analysis, hypotheses and classical assumptions were tested. The results showed that tax avoidance was not affected by leverage, business size, or profitability.